Regionalizing Resilience to Acute Meteorological Events: Comparison of Regions in the U.S. - Summers, Kevin; Harwell, Linda; Smith, Lisa M.; Buck, Kyle D. (Frontiers in Environmental Science, 2018)
Using a Climate Resilience Screening Index (CRSI) that was developed to represent resilience to acute weather events at multiple scales for the United States, nine regions of the United States are compared for resilience for these types of natural hazards. The comparison examines the domains, indicators and metrics of CRSI addressing environmental, economic and societal aspects of resilience to acute climate events. The index uses indicators and metrics that assess ecosystem, economic, governance and social services at county scales. The index was applied at the county scale and aggregated to represent select regions of the United States. Comparisons showed higher levels of resilience in the Northeast and West while counties in the Southeast and South-Central regions exhibited lower resilience to acute climate events.